Association of CD103+ T cell infiltration with overall survival in solid tumors of the digestive tract and its potential in anti-PD-1 treatment: A review and meta-analysis - Wei, Wei; Ding, Yun; He, Jiajia; Wu, Jun (Biomedical papers, 2022)
We looked into the most recent studies of digestive tumor patients and performed a meta-analysis to explore the association of CD103+ T cell infiltration with overall survival (OS) in solid tumors of the digestive duct. Major databases were searched. The hazard ratios (HR) and 95% confidence intervals (CI) for overall survival were extracted and pooled. A total of 1915 patients from 11 cohorts were included into the present meta-analysis. The pooled HR was 0.64 (95% CI: 0.42-0.96, P=0.03), suggesting that high CD103+ T cell infiltration is associated with better prognosis. Yet significant heterogeneity was revealed and located in the subgroup of CD4+CD103+ T cells. The pooled result indicated that CD103+ T cell infiltration in solid tumors of the digestive duct may possess predictive value for prognosis. Preclinical studies suggested that CD103+ T cell infiltration could predict response to anti-PD-1/PD-L1 treatment.
Keywords: CD103+ T cell; digestive tumor; prognosis